Going Beyond (Cultural) Soft Power: The Political Economy of Hollywood in Cold War (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
The notion of cultural soft power has always been addressed as the use of one film industry for the sake of a state’s soft power in international politics. However, the idea of a state–film industry combination omits and treats the two entities with identical and similar interests or powers. Confronting this conceptualization, this research uses an inductive methodology in its conceptual paper, which criticizes the existing concept and provides a new framework for analysis. This research offers a new conceptual framework to understand the seemingly combined nature of the film industry and state in world politics and to treat them as two distinct entities with different logics and interests. To do so, this paper proposes the use of the political economy approach to the film industry and Foucault’s governmentality for state rationality. Taking the case of Hollywood during the Cold War, this research argues that the combination of the state and film industry could only be realized in terms of industry profitability and the enhancement of the state’s images toward the international population. In other words, while the film industry will only want to propagate the state’s images in its international market because it is profitable, the state is equipped with various tools to create such conditions.